Análisis a los estados financieros de la “Cooperativa de Transporte Interprovincial Putumayo”, provincia de Sucumbíos, cantón Lago Agrio, periodo 2011 - 2012. - Uchubanda Noboa, Marcia Leonor (2014)
The completion of the thesis, ANALYSIS OF FINANCIAL STATEMENTS "INTER COOPERATIVE TRANSPORTATION PUTUMAYO" SUCUMBÍOS province, SOUR LAKE CANTON, PERIOD 2011 - 2012, was made based on the information provided by the Manager and the Financial entity, which has shown the economic reality of the company in addition to being a relevant and feasible topic prior to obtaining in Accounting and Auditing Accountant CPA thesis. In compliance with the goals outlined in the research project, the Vertical and Horizontal Analysis making representation and verification of accounts, where we observed the increases and decreases that have existed from year to year, just as was done was analyzed expenditure for the period administrative, financial indicators was applied, which was denoted that the Bank has a high value in Current Assets, Working Capital Liquidity, Strength, Low Debt Index, Index Working Capital I do not have the return on sales, return on equity and return on capital paid under. As recommended management policies that help improve the economic situation of the cooperative and thus continue serving Citizenship.